(untitled) (Journal of Bangladesh Academy of Sciences, 2023)
This article provides an overview of the rich chemistry of rhenium and manganese decacarbonyls, M2(CO)10 (M = Re, Mn) and their acetonitrile derivatives [M2(CO)8(NCMe)2] as precursors for synthesis of new di‒, tri‒ and tetranuclear complexes derived from a wide range of heterocyclic thiols such as pyridine-2-thiol, pyrimidine-2-thiol, tetrahydropyrimidine-2-thiol, 2-mercapto-1-methylimidazole, benzimidazole-2-thiol etc. A comparative study of the reactivities of these complexes with various mono and bidentate ligands is also the subject of this review. In some instances, the structural aspects of the complexes are also discussed. The applications of these complexes as precursors for the synthesis of a wide variety of mixed-metal cluster complexes are highlighted. J. Bangladesh Acad. Sci. 47(1); 1-20: June 2023